Water quality as a limiting factor: Concepts and applications for the Mid-Ebro valley - Jorge Bielsa; Julio Sanchez-Choliz (European Regional Science Association (ERSA), 1998)
The particular characteristics of the soil, the climate and the distrubution of water amongst the different types of use, all result in a specific problem for the management of the water resource in the arid and semi-arid areas of Spain, making it necessary to redefine tha notions of consumption, efficiency of use and water supply in accordance with new criteria that take the different qualities into account. This, in turn, leads to new meanings being given to terms such as scarcity, water deficit, etc. Within this framework, the objetive of the paper is twofold: first, to propose new concepts and measures that include qualitative aspects; secondly, to psesent an empirical approximation of these concepts, based on the water and socio-economic data for tha mid-Ebro Valley region of Northern Spain. Keywords: Water Economics, Water supply, Water management.
Keywords: 330